Pengaruh Bimbingan Kelompok Teknik Modeling Simbolik Terhadap Perkembangan Akhlak Siswa - Triyani Widyastuti; Anwar Sutoyo (Indonesian Journal of Counseling and Development, 2021)
This study was conducted based on the phenomenon that occurs in fifth grade of SDN 03 Sumurjomblangbogo which shows a low student moral development equality the messenger of Allah SWT, Rasulullah SAW, fellow human beings, created alone and in a calm environment. The purpose of this study was to prove whether or not the influence of group guidance with symbolic modeling techniques on student moral development. The type of this study was one-group experimental pre-test post-test design. This study was conducted in eight meetings with 10 students as a subject. The technique of data analysis used descriptive percentage analysis and wilcoxon test. This study showed that there was a change in the level of moral development of students before and after participating in group guidance services with symbolic modeling techniques that increased by an average 14.3% from the initial results during the pre-test of 62.5% to 76.8% at post-test. Additionally, data obtained from wilcoxon pairs match with n-10 significant 5% obtained with thitung < ttabel (0<8) or Ho is rejected and Ha is accepted. This shows that the group guidance services with symbolic modeling techniques affect the moral development in fifth grade students of SDN 03 Sumurjomblangbogo